Two-photon excitation fluorescence microspectroscopy protocols for examining fluorophores in fossil plants - Michael R. Stoneman; Victoria E. McCoy; Carole T. Gee; Katherine M. M. Bober; Valerică Raicu (Communications Biology, 2024)
Abstract Fluorescence emission is common in plants. While fluorescence microscopy has been widely used to study living plants, its application in quantifying the fluorescence of fossil plants has been limited. Fossil plant fluorescence, from original fluorophores or formed during fossilization, can offer valuable insights into fluorescence in ancient plants and fossilization processes. In this work, we utilize two-photon fluorescence microspectroscopy to spatially and spectrally resolve the fluorescence emitted by amber-embedded plants, leaf compressions, and silicified wood. The advanced micro-spectroscope utilized, with its pixel-level spectral resolution and line-scan excitation capabilities, allows us to collect comprehensive excitation and emission spectra with high sensitivity and minimal laser damage to the specimens. By applying linear spectral unmixing to the spectrally resolved fluorescence images, we can differentiate between (a) the matrix and (b) the materials that comprise the fossil. Our analysis suggests that the latter correspond to durable tissues such as lignin and cellulose. Additionally, we observe potential signals from chlorophyll derivatives/tannins, although minerals may have contributed to this. This research opens doors to exploring ancient ecosystems and understanding the ecological roles of fluorescence in plants throughout time. Furthermore, the protocols developed herein can also be applied to analyze non-plant fossils and biological specimens.